“The loneliest spot on Earth”: Harry Mulisch’s Literary Experiment in Criminal Case 40/61 - Bax, Sander (Department of Dutch and South African Studies, Faculty of English, 2012)
Harry Mulisch’s Criminal Case 40/61 is often regarded as an early representative of the movement of New Journalism and as an example for what we nowadays call ‘literary non-fiction.’ In this essay, I will argue that this classification does not do justice to the complexity of the literary experiments that Mulisch is trying out in this text. In Criminal Case 40/61 Mulisch develops a highly personal and literary way to write about Adolf Eichmann. A problem as complex as the essence of evil, he claims, can not be comprehended with the methods of journalism and history only, the Eichmann enigma calls for a new language. I will outline a number of techniques Mulisch used to achieve this goal. In this text, Mulisch uses an autofictional construction as well as a metaphorical way of thinking and writing that transgresses the journalistic or historicist mimetic-referential and discursive ways of writing. Central to Mulisch’s literary method are two principles: that of the invention of language and images and that of radical identification.
Keywords: literary non-fiction; New Journalism; fictionality; autofiction; Harry Mulisch; Adolf Eichmann